1998
DOI: 10.1111/j.2044-8260.1998.tb01289.x
|View full text |Cite
|
Sign up to set email alerts
|

Drawing conclusions: A re‐examination of empirical and conceptual bases for psychological evaluation of children from their drawings

Abstract: Children's drawings on their own are too complexly determined and inherently ambiguous to be reliable sole indicators of the emotional experiences of the children who drew them. Further research is needed to establish the extent to which such drawings can usefully facilitate assessment of children by other means or provide useful support as one of several converging lines of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
121
2
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(127 citation statements)
references
References 14 publications
1
121
2
3
Order By: Relevance
“…The findings of this study suggest that the majority of effects reported in previous studies are not necessarily an artefact of the methodological limitations noted by Freeman (1976), Cox (1992), Jolley (1995) and Thomas and Jolley (1998). While the precise nature of the mechanisms which are responsible for these effects remains elusive and must be a subject for future research, this experiment has provided unambiguous evidence that, contrary to the assertions of some recent researchers, size and colour changes in relation to affective characterisation do indeed occur, and that these phenomena require further investigation.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…The findings of this study suggest that the majority of effects reported in previous studies are not necessarily an artefact of the methodological limitations noted by Freeman (1976), Cox (1992), Jolley (1995) and Thomas and Jolley (1998). While the precise nature of the mechanisms which are responsible for these effects remains elusive and must be a subject for future research, this experiment has provided unambiguous evidence that, contrary to the assertions of some recent researchers, size and colour changes in relation to affective characterisation do indeed occur, and that these phenomena require further investigation.…”
Section: Discussionsupporting
confidence: 52%
“…As Thomas and Jolley (1998) point out, the interpretation of size changes in children's drawings is a complex process, as a reduction or an increase in the size of a feature may be a positive sign in one child's drawings and a negative sign in the next child's drawing of the same topic. However, the existing literature (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The validity of human figure drawing test scores is debated (Gresham, 1993;Motta, Little, & Tobin, 1993a, 1993b, but only with respect to behavioral risk assessment using particular features of the human figure as indicators of disturbed emotions (Aldridge et al, 2004;Bekhit, Thomas, & Jolley, 2005;Lange-Küttner, 1989;ter Laak, de Goede, Aleva, & van Rijswijk, 2005;Thomas & Jolley, 1998). In young children, drawing recognizable human figures requires the ability to follow simple response rules (Riggs, Jolley, & Simpson, 2013).…”
mentioning
confidence: 99%